Reverse spherification technique / Farhan Faat and Mohamad Farhan Azmi - Faat, Farhan; Azmi, Mohamad Farhan (Faculty of Hotel & Tourism Management, UiTM Pulau Pinang, 2019)
Living in this modern era and with the advancement of technology today, there is nothing seems to be impossible in culinary world. What we see today might never be realized in the old days. It all started when two physicists Nicholas Kurti and Herve in 1988 coined a new approach known as molecular gastronomy. This knowledge has created a new scientific study to investigate culinary transformation, specifically the chemistry and physics behind food preparation. Collaboration between scientist and talented chefs has created a new exhilarating phenomenon in culinary world. Starting from a basic need to understand molecular level of a product, they found a new approach and ways to enjoy and experience foods. This knowledge has been widely used in the early of 2000 by prominent chefs like Heston Bluementhal, Ferran Andria, Pierre Gagniere and Grant Achatz. Restaurants which applied molecular knowledge in cooking were listed and won The World's 50 Best Restaurant.